ACUTE VASCULAR COMPLICATIONS FOLLOWING PERCUTANEOUS CORONARY INTERVENTIONS (PCI): MECHANISMS, PREVENTION, AND THERAPEUTIC STRATEGIES - Woźniak, Dominik; Kwiatkowska, Aleksandra; Dubiel , Mikołaj; Sanakiewicz, Sylwia; Obajtek, Patryk (International Journal of Innovative Technologies in Social Science, 2026)
Percutaneous coronary intervention (PCI) has become one of the most commonly performed cardiovascular procedures worldwide and represents a cornerstone therapy for the treatment of coronary artery disease and acute coronary syndromes. Over the past decades, significant technological and pharmacological advances have improved the safety and effectiveness of PCI procedures. Despite these developments, acute vascular complications remain an important clinical concern and may negatively affect procedural success and long-term outcomes. Acute complications associated with PCI include coronary artery dissection, coronary perforation, acute vessel closure, stent thrombosis, and bleeding events related to vascular access or antithrombotic therapy. Although the overall incidence of such complications has declined with the introduction of modern drug-eluting stents, intravascular imaging, and radial artery access techniques, the increasing complexity of treated coronary lesions continues to present challenges for interventional cardiologists. This review provides a comprehensive overview of the mechanisms, epidemiology, risk factors, prevention strategies, and management approaches for acute vascular complications following PCI. The analysis integrates findings from contemporary clinical trials, meta-analyses, international registries, and guideline documents. Particular attention is given to complications occurring during complex procedures such as chronic total occlusion interventions and treatment of heavily calcified coronary lesions. Understanding the mechanisms underlying PCI-related complications and implementing appropriate preventive strategies are essential for improving procedural safety and optimizing clinical outcomes in patients undergoing coronary revascularization.